Identity and drug abuse in adolescents - Molla Madueño, Miguel Angel (2011)
In the present study evaluation of the identity in adolescents was carried out, on the base of Erik Erikson’s evolutionary theory. The sample was made by 68 male and female adolescents, 40 students from Secondary Institution and 28 from a therapeutic program for adolescents with drug problems, from Madrid, Spain. The objective of the study was to understand the factors participating in personal identity and his crisis. The study mentions that personal identity development will be benefited by the ability to learn about oneself and to understand the own identity process. The results show that personal identity development jeopardizes by the presence of conflicts in the integration of new emotional experiences. The total of the identity, learning and laboriousness’ scale is affected for low achievement of temporal perspective and the lack of integration as well as assimilation of experiences. The temporal perspective was considered as a key element for the prevention of the improper drug use among the adolescents in our sample.